Evaluación agronómica del cultivar de Cannabis sativa L. "Cannawine INTA-ACCS" en Patagonia Norte Argentina - Calzolari, Gabriela; Kandus, Mariana Virginia; Gomez, Roberto Carlos; Buda, Vicente Sebastián; Aguirre, Roxana; Juarez, Santiago; Mazzoni, Ariel Omar; Amorosi, Mariana Lorena (Universidad Nacional del Comahue, 2025)
Póster y resumen